1/(1+x^2)√(4+3x^2)[-∞,∞]などの定積分

\begin{alignat}{2}
&(1)  \displaystyle\int_0^{\infty} \frac{x^{μ-1}}{\sqrt{1+x^v}}dx=\frac{1}{v}B\left(\frac{μ}{v},\frac{1}{2}-\frac{μ}{v}\right)  (0 \lt 2μ \lt v)\\
&(2)  \displaystyle\int_{-\infty}^{\infty} \frac{1}{(1+x^2)\sqrt{b+ax^2}}dx=
\begin{cases}
\displaystyle \frac{2}{\sqrt{b-a}} \tan^{-1} \sqrt{\frac{b}{a}-1}  (a \lt b)\\
\displaystyle \frac{2}{\sqrt{a}}  (a=b)\\
\displaystyle \frac{1}{\sqrt{a-b}}\log \frac{\sqrt{a}+\sqrt{a-b}}{\sqrt{a}-\sqrt{a-b}}  (a \gt b)\\
\end{cases}\\
&(3)  \displaystyle\int_{-\infty}^{\infty} \frac{1}{(1+x^2)\sqrt{4+3x^2}}dx=\frac{π}{3}\\
&(4)  \displaystyle\int_{-\infty}^{\infty} \frac{1}{(1+x^2)\sqrt{4+9x^2}}dx=\frac{4}{\sqrt{5}}\log φ\\
&(5)  \displaystyle\int_{-\infty}^{\infty} \frac{1}{(1+x^2)\sqrt{4+5x^2}}dx=2\log φ\\
&(6)  \displaystyle\int_{-\infty}^{\infty} \frac{1}{(1+x^2)\sqrt{1+5x^2}}dx=3\log φ
\end{alignat}








<証明>

\((1)\) \(x^v=t\) と置きます。\((vx^{v-1}dx=dt)\)
\begin{alignat}{2}
\displaystyle\int_0^{\infty} \frac{x^{μ-1}}{\sqrt{1+x^v}}dx&=\displaystyle\int_0^{\infty} \frac{t^{\frac{μ-1}{v}}}{\sqrt{1+t}} \cdot \frac{1}{vt^{\frac{v-1}{v}}}dt\\
&=\frac{1}{v}\displaystyle\int_0^{\infty} \frac{t^{\frac{μ}{v}-1}}{\sqrt{1+t}}dt=\frac{1}{v}B\left(\frac{μ}{v},\frac{1}{2}-\frac{μ}{v}\right)\\
\end{alignat}以上より$$\displaystyle\int_0^{\infty} \frac{x^{μ-1}}{\sqrt{1+x^v}}dx=\frac{1}{v}B\left(\frac{μ}{v},\frac{1}{2}-\frac{μ}{v}\right)  (0 \lt 2μ \lt v)$$







$$(2)  \displaystyle\int_{-\infty}^{\infty} \frac{1}{(1+x^2)\sqrt{b+ax^2}}dx=2\displaystyle\int_0^{\infty} \frac{1}{(1+x^2)\sqrt{b+ax^2}}dx$$\(\displaystyle x=\sqrt{\frac{b}{a}}t\) と置きます。\(\displaystyle \left( dx=\sqrt{\frac{b}{a}}dt\right)\)$$=2 \displaystyle\int_0^{\infty} \frac{1}{\left(1+\frac{b}{a}t^2\right)\sqrt{b+bt^2}}\cdot \sqrt{\frac{b}{a}}dt=2\sqrt{a} \displaystyle\int_0^{\infty} \frac{1}{(a+bt^2)\sqrt{1+t^2}}dt$$\(t=\tan r\) と置きます。\(\displaystyle \left(dt=\frac{1}{\cos^2 r}dr\right)\)
\begin{alignat}{2}
&=2\sqrt{a}\displaystyle\int_0^{\frac{π}{2}} \frac{1}{(a+b \tan^2 r)\sqrt{1+\tan^2 r}} \cdot \frac{1}{\cos^2 r}dr\\
&=2\sqrt{a}\displaystyle\int_0^{\frac{π}{2}} \frac{1}{(a+b \tan^2 r) \cos r}dr\\
&=2\sqrt{a} \displaystyle\int_0^{\frac{π}{2}} \frac{\cos r}{a \cos^2 r+b \sin^2 r}dr=2\sqrt{a} \displaystyle\int_0^{\frac{π}{2}} \frac{\cos r}{a-(a-b)\sin^2 r}dr\\
\end{alignat}\(\sin r=u\) と置きます。\((\cos rdr=du)\)$$=2\sqrt{a}\displaystyle\int_0^1 \frac{1}{a-(a-b)u^2}du$$

\((A)\) \(a \lt b\) のとき$$=2\sqrt{a}\displaystyle\int_0^1 \frac{1}{a+(b-a)u^2}du=2\sqrt{a}\left[\frac{1}{a}\cdot \frac{1}{\sqrt{b-a}} \tan^{-1}\sqrt{\frac{b-a}{a}}u\right]_0^1=\frac{2}{\sqrt{b-a}} \tan^{-1} \sqrt{\frac{b}{a}-1}$$\((B)\) \(a=b\) のとき$$=2\sqrt{a}\displaystyle\int_0^1 \frac{1}{a}du=\frac{2}{\sqrt{a}}$$\((C)\) \(a \gt b\) のとき
\begin{alignat}{2}
&=-2\sqrt{a} \cdot \frac{1}{a-b}\displaystyle\int_0^1 \frac{1}{u^2-\frac{a}{a-b}}du\\
&=-\sqrt{a} \cdot \frac{1}{a-b} \cdot \frac{1}{2\sqrt{\frac{a}{a-b}}}\left[\log \left|\frac{u-\sqrt{\frac{a}{a-b}}}{u+\sqrt{\frac{a}{a-b}}}\right|\right]_0^1\\
&=-\frac{1}{\sqrt{a-b}}\log \left| \frac{1-\sqrt{\frac{a}{a-b}}}{1+\sqrt{\frac{a}{a-b}}}\right|=\frac{1}{\sqrt{a-b}}\log \frac{\sqrt{a}+\sqrt{a-b}}{\sqrt{a}-\sqrt{a-b}}\\
\end{alignat}以上より
\begin{alignat}{2}
&\displaystyle\int_{-\infty}^{\infty} \frac{1}{(1+x^2)\sqrt{b+ax^2}}dx=
\begin{cases}
\displaystyle \frac{2}{\sqrt{b-a}} \tan^{-1} \sqrt{\frac{b}{a}-1}  (a \lt b)\\
\displaystyle \frac{2}{\sqrt{a}}  (a=b)\\
\displaystyle \frac{1}{\sqrt{a-b}}\log \frac{\sqrt{a}+\sqrt{a-b}}{\sqrt{a}-\sqrt{a-b}}  (a \gt b)\\
\end{cases}
\end{alignat}







\((3)\) \((2)\) で \(a=3,\,b=5\) とします。
\begin{alignat}{2}
\displaystyle\int_{-\infty}^{\infty} \frac{1}{(1+x^2)\sqrt{4+3x^2}}dx&=\frac{2}{\sqrt{4-3}}\tan^{-1}\sqrt{\frac{4}{3}-1}\\
&=2\tan^{-1}\frac{1}{\sqrt{3}}=2 \cdot \frac{π}{6}=\frac{π}{3}\\
\end{alignat}







\((4)\) \((2)\) で \(a=9,\,b=4\) のとき
\begin{alignat}{2}
\displaystyle\int_{-\infty}^{\infty} \frac{1}{(1+x^2)\sqrt{4+9x^2}}dx&=\frac{1}{\sqrt{9-4}}\log \frac{\sqrt{9}+\sqrt{9-4}}{\sqrt{9}-\sqrt{9-4}}=\frac{1}{\sqrt{5}}\log \frac{3+\sqrt{5}}{3-\sqrt{5}}\\
&=\frac{1}{\sqrt{5}}\log \frac{(3+\sqrt{5})^2}{4}=\frac{1}{\sqrt{5}}\log \left(\frac{3+\sqrt{5}}{2}\right)^2\\
&=\frac{1}{\sqrt{5}}\log φ^4=\frac{4}{\sqrt{5}}\log φ\\
\end{alignat}






\((5)\) \((2)\) で \(a=5,\,b=4\) のとき
\begin{alignat}{2}
\displaystyle\int_{-\infty}^{\infty} \frac{1}{(1+x^2)\sqrt{4+5x^2}}dx&=\frac{1}{\sqrt{5-4}}\log \frac{\sqrt{5}+\sqrt{5-4}}{\sqrt{5}-\sqrt{5-4}}=\log \frac{\sqrt{5}+1}{\sqrt{5}-1}\\
&=\log \frac{(1+\sqrt{5})^2}{4}=\log \left(\frac{1+\sqrt{5}}{2}\right)^2\\
&=\log φ^2=2\log φ\\
\end{alignat}







\((6)\) \((2)\) で \(a=5,\,b=1\) のとき
\begin{alignat}{2}
\displaystyle\int_{-\infty}^{\infty} \frac{1}{(1+x^2)\sqrt{1+5x^2}}dx&=\frac{1}{\sqrt{5-1}}\log \frac{\sqrt{5}+\sqrt{5-1}}{\sqrt{5}-\sqrt{5-1}}=\frac{1}{2}\log \frac{\sqrt{5}+2}{\sqrt{5}-2}\\
&=\frac{1}{2}\log (2+\sqrt{5})^2=\frac{1}{2}\log φ^6=3 \log φ
\end{alignat}

コメントを残す

メールアドレスが公開されることはありません。 * が付いている欄は必須項目です